2020
DOI: 10.3174/ajnr.a6563
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Health Care Use and COVID-19

Abstract: Indicates open access to non-subscribers at www.ajnr.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…In the period of our study, 1.4% of the patients with COVID-19 presented a stroke. There have been reported an incidence of stroke in COVD-19 patients from 0.19% to 5.4% and by Klok et al of 1.6% and 2.5% by Lodigiani et al, (13,14,15). Our study reported most of the cases were ischemic strokes.…”
Section: Discussionsupporting
confidence: 59%
“…In the period of our study, 1.4% of the patients with COVID-19 presented a stroke. There have been reported an incidence of stroke in COVD-19 patients from 0.19% to 5.4% and by Klok et al of 1.6% and 2.5% by Lodigiani et al, (13,14,15). Our study reported most of the cases were ischemic strokes.…”
Section: Discussionsupporting
confidence: 59%
“…Emergency infection protocols should be instituted by hospital to contain COVID-19. Clinical inpatient and outpatient services should be adjusted and all non-essential visits should be suspended ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Published data have demonstrated that the SARS-CoV-2 (COVID-19) pandemic has affected the US healthcare system in unique respects. Infection control measures, such as social distancing, lockdowns, the use of telemedicine, and modifications in clinical inpatient as well as outpatient services, were implemented across the country [ 1 ]. Moreover, patients have been encouraged to avoid hospitals except for true emergencies [ 2 , 3 ] and to use telephone hotlines for symptom screening instead of presenting for in-person evaluation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%